2008
DOI: 10.1007/s10397-008-0424-8
|View full text |Cite
|
Sign up to set email alerts
|

Early experience of laparoscopically assisted radical vaginal hysterectomy (Coelio-Schauta) versus abdominal radical hysterectomy for early stage cervical cancer

Abstract: The objective of this study was to compare outcomes of laparoscopically assisted radical vaginal hysterectomy (LARVH) vs. abdominal radical hysterectomy (RH) for early-stage cervical cancer. This is a retrospective study of all LARVH and RH procedures between January 2003 and June 2006 in our tertiary referral centre. Demographic, intraoperative and postoperative parameters in both groups were compared. Fourteen women (stage IA2-IB) underwent LARVH, and 12 women (stage IA2 to IB) had RH. All had clear excision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…A total of 1765 relevant studies were screened, of which 41 studies between 2002 and 2021, met the inclusion criteria and were involved in the meta‐analysis. 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 Data obtained from these studies were shown in Table 2 . The selected studies included 10 231 subjects with cervical cancer at the baseline of the studies; 4307 of them were using minimally invasive surgery, and 5924 were using laparotomy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 1765 relevant studies were screened, of which 41 studies between 2002 and 2021, met the inclusion criteria and were involved in the meta‐analysis. 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 Data obtained from these studies were shown in Table 2 . The selected studies included 10 231 subjects with cervical cancer at the baseline of the studies; 4307 of them were using minimally invasive surgery, and 5924 were using laparotomy.…”
Section: Resultsmentioning
confidence: 99%
“…The current meta‐analysis involved 10 231 subjects with cervical cancer at the baseline of the studies; 4307 of them were using minimally invasive surgery, and 5924 were using laparotomy. 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 The minimally invasive surgery had significantly lower wound infection, and postoperative complications in subjects with cervical cancer compared with laparotomy. However, minimally invasive surgery compared with laparotomy in subjects with cervical cancer had no significant difference in intraoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Our case–control study compared 14 women undergoing LARVH with 12 women undergoing RAH and suggested greater postoperative urinary tract dysfunction following RAH than after LARVH, with shorter hospital stay after LARVH (4.4 days [LARVH] versus 7.9 days [RAH]) 2 . Intraoperative injuries were higher in the LARVH group early in the learning curve but this is not reflected in our larger series (manuscript in preparation).…”
mentioning
confidence: 80%
“…In the GOG LAP 2 study, comparing laparoscopy vs laparotomy in the surgical staging of corpus cancer, women with BMI > 35 were initially excluded from the study and BMI was subsequently identified as a major risk factor for conversion to laparotomy with a conversion rate of 34.7% for institutions recruiting more than 300 women with a mean BMI of 31.9 . In the pre‐robotic era at our centre, women with cervix and endometrial cancers were offered laparoscopic surgery provided they had adequate vaginal access . However, by default, morbidly obese women were offered open surgery.…”
Section: Discussionmentioning
confidence: 99%